THE GEOLOGY AND ECONOMIC POTENTIAL OF SOME CARBONATE ROCKS IN THE GUNUNG KANTHAN AREA - BINTI CHE SOPA, NOR EZZA (Universiti Teknologi PETRONAS, 2015)
This project is about the geology and economic potential of some carbonates rocks in the Gunung Kanthan area. The area is mostly made up of limestone hills that were remnants of massive carbonate beds covered with alluvial sediments. This research is aimed at improving the knowledge and the geology of Gunung Kanthan and economic potential of the area. This study includes the lithostratigraphic log and the geological map of Sungai Siput that is focusing on Gunung Kanthan at 1:10 000. A number of geochemical tests such as XRF, thin section analysis, rock aggregate test, whiteness test, thermal conductivity and total organic carbon test. Based on the tests, it is concluded that the limestone of this area has a high economic potential to be used in construction industries. In conclusion, it is evident that limestones especially in Gunung Kanthan are good in quality for economic purposes.